HISTORICAL THINKING ABILITY IN BUILD HISTORICAL EMPATHY (CASE STUDY: HISTORY EDUCATION STUDENTS OF JAKARTA STATE UNIVERSITY) - Lobelia Asmaul Husna; Abdul Syukur; Umasih Umasih (Candrasangkala: Jurnal Pendidikan dan Sejarah, 2020)
This study aims to study the ability of historical thinking in building historical empathy for the history education students at Universitas Negeri Jakarta. The study was held in semester 112 in class C batch 2018 course of Indonesian history of The Colonial period and class A batch 2017 course of Indonesian history of New Order and Reformation period. This research uses qualitative methods with a case study approach. Data collection techniques used are interviews and documentation. The result of this study is that students of history education have diverse abilities in historical thinking skills. However, on the ability of historical empathy ̧ the entire student history has cognitive empathy. This means students are able to understand the emotions, situations, and conditions of historical figures in the past. In addition, on the ability of cognitive empathy students are able to be objective so that on the understanding of history, students are not on the sides of one figure only